Hul'qumi'num peoples in the Gulf Islands: re-storying the Coast Salish landscape - Abramczyk, Ursula (2017)
A negotiated, cooperative co-management arrangement between six Coast Salish First Nations and Parks Canada has created an opportunity for Hul’qumi’num peoples to “re-story” a colonized landscape in the southern Gulf Islands archipelago east of Vancouver Island, British Columbia. Collaborative research undertaken with the Hul’qumi’num-Gulf Islands National Park Reserve Committee is part of a long-term and practical effort to regain authorship over Central Coast Salish cultures, languages and history. In particular, this thesis seeks to challenge popular and public narratives which do not recognize Hul’qumi’num peoples’ territories and territorialities in the Gulf Islands National Park Reserve (GINPR). By tracing the processes of narrative and historical production, and with attention to how power imbues these processes (Trouillot 1995), I argue that the narrative of ephemerality whereby Hul’qumi’num peoples are thought to have “floated by” the southern Gulf Islands, but never “settling” there, emerged largely through early colonial processes and Indian land policy which reconfigured Central Coast Salish territorialities. These assumptions have been reproduced in a regional anthropological “seasonal rounds” narrative and through the language of “villages” and “seasonal camps.” Through the period of comprehensive land claims, this narrative has been reified by framing the southern Gulf Islands as the exclusive territory of First Nations’ neighbouring the Hul’qumi’num. Narratives of ephemerality and exclusivity continue to dominate the public imaginary through their reproduction in GINPR interpretive materials and in the grey literature of consulting archaeologists. These narratives are not neutral, but have implications for rights and title recognition and accommodation by the state. The perspectives of Hul’qumi’num peoples help to understand the silence in the dominant narratives by elucidating the historic and ongoing significance of specific locales in the southern Gulf Islands for Hul’qumi’num individuals, ...